2010
DOI: 10.1007/s10722-010-9616-y
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite marker based analysis of genetic diversity in short day tropical Indian onion and cross amplification in related Allium spp.

Abstract: This paper deals with the diversity assessment of tropical Indian onion and cross amplification of genomic and EST-SSR markers in distantly related native wild species. Out of 60 SSRs, 10% genomic SSRs were able to amplify as compared to EST-SSR where 53.3% primers were able to reveal amplicons. Clustering revealed five groups and indigenous short day onion formed separate cluster from the exotic short day and long day onions. A. roylei accessions exhibited a dissimilarity index of 35.5% between themselves whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
38
7
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 35 publications
12
38
7
3
Order By: Relevance
“…The ACM238 produced the highest number of bands (14). The EST-SSRs markers showed a higher percentage of amplification than in previous reports (Jakše et al 2005;Khar et al 2011;Mallor et al 2014;Mitrová et al 2015). The bands of ACM315 (290 bp), ACM238 (153 bp) and ACM300 (184 bp, 207 bp, 216 bp) were excluded from further evaluation because of being monomorphic across the studied set of 96 accessions.…”
Section: Resultsmentioning
confidence: 72%
“…The ACM238 produced the highest number of bands (14). The EST-SSRs markers showed a higher percentage of amplification than in previous reports (Jakše et al 2005;Khar et al 2011;Mallor et al 2014;Mitrová et al 2015). The bands of ACM315 (290 bp), ACM238 (153 bp) and ACM300 (184 bp, 207 bp, 216 bp) were excluded from further evaluation because of being monomorphic across the studied set of 96 accessions.…”
Section: Resultsmentioning
confidence: 72%
“…Jakse et al (2005) identified 398 SNP, indels and SSRs which distinguished 35 elite onion populations. The diversity assessment of tropical Indian onion and cross amplification of genomic and expressed sequence tag (EST)-SSR markers in distantly related native wild species were estimated (Khar et al 2010) (Table 1).…”
Section: Diversity Analysis and Varietal Identification Of Alliumsmentioning
confidence: 99%
“…of onion diversity has not been fully exploited but with the liberalisation of policies multinational companies have entered in hybrid onion development (Khar et al 2010). Here we have reviewed the use of molecular markers for diversity analysis, varietal identification, colour and quality improvement, male sterility analysis and recent efforts of genome sequencing in Alliums.…”
mentioning
confidence: 99%
“…Other widely used markers like AFLP (Volk et al, 2004;García-Lampasona et al, 2012) and SSR (Fischer and Bachmann, 1998;Song et al, 2004;Khar et al, 2011;Lee et al, 2011;Cunha et al, 2012) have been used in the study of Allium. Initially, we also tried some SSR primers with our investigated species.…”
mentioning
confidence: 99%